KEWENANGAN PARTAI POLITIK DALAM PENARIKAN DUKUNGAN BAKAL PASANGAN CALON KEPALA DAERAH - Mutawalli, Muhammad; Moenta, Andi Pangerang; Hasrul, Muhammad (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2021)
This study aims to explain the political party authority in withdrawing support for the regional head candidate in elections, as well as providing an understanding of sanctions that targeted political parties who withdrawn or revoked their political stance by applicable regulations. This study using a legal perspective on the authority of political parties in withdrawing support and Authority Theory, Democracy Theory, Rule of Law Theory, Decision Making Theory, and Sanction Theory as supported theories. The formulation of all arguments, facts, and theoretical frameworks in this study uses empirical normative legal research methods. Data obtained and collected through books, journals, theses, and recent dissertations, interviews, and articles related to the problem. The research method in this study combines elements of normative and empirical law and data. This research is qualitative research used in library observation. This research concludes that the authority of political parties regarding the withdrawal of support for a prospective regional head candidate pair explained in three stages or processes, including the first stage is before registering candidates to the KPU, the second stage is the stage after registering with KPU, and last is the stage after the determination of a prospective pair of candidates by the KPU. Among the existing stages, there is a full space for political parties to participate and room for the KPU to organize regional head elections. So concerning the withdrawal of support, political parties are not allowed arbitrarily to withdraw or vice versa regarding their support for prospective pairs of candidates. Referring to the applicable regulations, the forms of sanctions that can be given to political parties that withdraw or revoke a candidate pair are criminal sanctions and administrative sanctions. Where administrative sanctions are considered to be less firm against political parties, in contrast to criminal sanctions (ultimum remedium) or as a last resort that is much firmer but only aimed at the leaders or leaders of the heads of the central political parties who deliberately make withdrawals. Keyword: Political Parties, Withdrawal of Support, Prospective Regional Head Candidates.